THE REDUCTION OF ANXIETY AND PAIN DURING VENOUS BLOOD SAMPLING USING HYPNO-EFT (EMOTIONAL FREEDOM TECHNIQUES) METHOD - Navianti, Diah; Garini, Ardiya; Karneli, Karneli (YCAB Publisher & IAKMI SULTRA, 2018)
Background: Venous blood sampling has several risks of complication, the basic cause was emotional factor, such as anxiety and pain, which remain important to be solved. Objective: The aim of this study was to determine the effect of hypno–EFT to reduce the anxiety and pain during venous blood sampling. Methods: The design of the study was quasi experimental, with pretest posttest with control group design. The sampling technique was simple random sampling to select 52 respondents. Anxiety was measured using a Hamilton anxiety rating scale (HARS) modification and pain was measured using the Visual analogue scale (VAS) method. Wilcoxon and Manova multivariate test were used for data analysis.Results: Before hypno-EFT there was 1 person (2.9%) did not experience anxiety, 9 people (25.7%) with mild anxiety, 20 people (57.1%) with moderate anxiety and 5 people (14.3%) with severe anxiety. After hypno-EFT therapy, there were 23 people (65.7%) did not get anxiety, mild anxiety were 11 people (31.4%) and severe anxiety was found in 1 person (2.9%). For the average pain of respondent in venipuncture before hypno-EFT was 3.20 with a median 3.00 and a standard deviation was 1.91. The minimum value of pain was 0 and 9 in maximum. After therapy Hypno-EFT, the average pain was 1.54 and the minimum value of pain was 0 and 6 at maximum. Statistical result showed that the p-value of anxiety and pain was 0.000 (<0.05)Conclusion: There was a significant effect of hypno-EFT therapy to decrease the anxiety and pain during venous blood sampling. This method is recommended as an alternative procedure in venous blood sampling with complicating factors.